Vocational interests of female computer programmers. - Perry, Dallis K.; Cannon, William M.; Perry, D K; Cannon, W M (Journal of Applied Psychology)
Scores of 293 female computer programmers on the SVIB for men were found to be quite similar to those of male programmers, although interests of the women were somewhat higher in aesthetic and scientific fields and lower in technical and technical-supervision occupations. Female programmers indicate interest in all forms of mathematics and lack of interest in people. A key composed of items with a 12% or larger difference between female programmers and other professional women showed a 20% overlapping of professional women in general with a cross-validation group of female programmers. Programmers who are dissatisfied with their occupation score significantly lower on the key than do satisfied programmers.